The Guanidine Riboswitch—A Poor Orphan No Longer. Issue 2 (16th February 2017) - Lilley, David M.J.
Abstract : Riboswitches are widespread in the bacterial kingdom, where they regulate gene expression in response to different small molecules and ions. However, some remain orphans with no known endogenous ligand. Three recently published papers (Battaglia et al., 2017; Nelson et al., 2017 ; andReiss et al., 2017 ) de-orphanize a widespread ykk C element, showing that it responds to guanidine and elaborating on how that response is mediated. Abstract : Riboswitches are widespread in the bacterial kingdom, where they regulate gene expression in response to different small molecules and ions. However, some remain orphans with no known endogenous ligand. Three recently published papers (Battaglia et al., 2017; Nelson et al., 2017; and Reiss et al., 2017) de-orphanize a widespread ykk C element, showing that it responds to guanidine and elaborating on how that response is mediated.